Menuju Smart Village Sinergi E-commerce dan Digital Marketing untuk Kesejahteraan Masyarakat Desa - Agung Baitul Hikmah Agung; Tuti Alawiyah Tuti; Haerul Fatah Haerul; Taufik Wibisono Taufik (Universitas Bina Sarana Informatika, 2024)
The growth of e-commerce has opened up opportunities for UMKM to expand their market and improve the welfare of rural communities. However, many UMKM do not yet understand their potential. This activity aims to help UMKM in Serang Village improve the marketing of their products through e-commerce and digital marketing training. The implementation method includes training materials and hands-on practice in creating e-commerce accounts, posting products, and copywriting. The output targets are increased participant knowledge of e-commerce and digital marketing, as well as the realization of Smart Village through the synergy of e-commerce and digital marketing to improve the welfare of rural communities. This activity is documented in the form of a video and published online. Keywords: Smart Village; E-commerce; Digital Marketing; UMKM